Jewels that made history : 100 stones, myths & legends - Volandes, Stellene (Rizzoli, 2020)
"An illustrated history of the greatest, most iconic, and interesting moments in jewelry of all time-from red carpet to royalty, Cleopatra to Lady Gaga"--